Profesi Pengrajin Batik Ditinjau dari Persepsi dan Motivasi: Studi Pada Batik Nila Kemilau Kecamatan Polokarto Kabupaten Sukoharjo - Hanafiah, Ulfah Nur; Maryam, Siti; Marwati, Fithri Setya (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to be able to see the influence of the batik craftsman profession in terms of perception and motivation (studies on Nila Kemilau batik, Polokarto District, Sukoharjo Regency). The method is by applying quantitative descriptive, through the population of the Polokarto sub-district who are aged 17-35 years and the sample is 100 respondents through a purposive sampling technique. Data was collected by applying a questionnaire, and then analyzed through reliability and validity tests, f and t tests, multiple linear regression analysis and the coefficient of determination. The result is that Perception has a significant and partial influence on the Profession, Motivation has a partial and significant influence on the Profession, Perception and Motivation have a significant and significant influence on the Profession. The result is R2 obtained 0.571. Which means that 57.1% of the professional variables can explain perception and motivation variables and the remaining 42.9% can explain other variables that have not been included in the research. Keywords: Profession, Perception, Motivation.